Evaluation of Proteins Released to Medium in Yeast-Bacteria Co-culture System - Çağatay Tarhan; Ayşegül Yanık (Journal of Advanced Research in Natural and Applied Sciences)
Cultivation of microorganisms in ideal laboratory conditions seperates them from their natural conditions and isolates them from their microbial world, especially from their competitors. With traditional pure culture-oriented cultuvation techniques, interactions mediated by small molecules are not taken into account, resulting in the precise nature of the interactions being largely unknown. Co-culture systems are systems in which two or more different cell populations are grown together. In this way, studies on natural interactions between populations can be made and synthetic interactions that are not observed in nature can be provided. With these systems, natural product discovery, microbial ecology, evolution and pathogenesis studies are carried out. In addition, co-culture systems are also used in industrial, environmental and medical studies. In this study, the wild strain of Schizosaccharomyces pombe and the DH5α strain of Escherichia coli were grown in their own specific media, then cultured for 48 hours and 72 hours by cultivating in media containing 0,1% glucose with different cell number, and finally the differentiation in the proteins released by the cells into the medium was observed in SDS polyacrylamide gels. Different from the control conditions, new protein bands that emerged under the co-culture conditions were detected and two of these bands were analyzed by mass spectrometry (MS). While 6 of differentaited proteins were released by S.pombe, 257 proteins matched with E.coli proteom. These proteins are; Various carbohydrate-binding proteins, membrane proteins involved in the identification of various signaling molecules and antibiotics, and other proteins involved in various cellular processes.